Application of Asteraceae biomass and biofertilizers to improve potato crop health by controlling black scurf disease - Rafiq, Muhammad; Shoaib, Amna; Javaid, Arshad; Parveen, Shagufa; Hassan, Muhammad Ahmad; Nawaz, Hafiz Husnain; Cheng, Chunsong (Frontiers in Plant Science, 2024)
Potato (Solanum tuberosum L.) cultivation in Pakistan faces challenges, with black scurf disease caused by Rhizoctonia solani Kühn being a significant concern. Conventional methods like chemical fungicides partially control it, but an effective solution is lacking. This study explores the potential of biofertilizers and soil amendments from Asteraceae weed biomass to manage the disease. Two potato varieties, Karoda and Sante, were chosen, and two biofertilizers, Fertibio and Feng Shou, were tested alone or with Xanthium strumarium biomass. Disease pressure was highest in the positive control, with significant reduction by chemical fungicide. X. strumarium biomass also decreased disease incidence significantly. Fertibio showed better efficacy than Feng Shou. Physiological and biochemical attributes of plants improved with biofertilizer and biomass application. Tuber weight, photosynthetic pigments, total protein content, and antioxidant enzymes (CAT, POX, and PPO) were positively correlated. Combined application of Fertibio and S. marianum biomass effectively managed black scurf disease. These eco-friendly alternatives could enhance disease management and yield. Future research should explore their cost-effectiveness, commercialization, and safety.